Effects of Common Anti-Inflammatories on Adenovirus Entry and Their Physicochemical Properties: An In-Depth Study Using Cellular and Animal Models - Hector R. Galvan-Salazar; Marina Delgado-Machuca; Gustavo A. Hernandez-Fuentes; Nomely S. Aurelien-Cabezas; Alejandrina Rodriguez-Hernandez; Idalia Garza-Veloz; Martha A. Mendoza-Hernandez; Margarita L. Martinez-Fierro; Sergio A. Zaizar-Fregoso; Iram P. Rodriguez-Sanchez; Fabian Rojas-Larios; Mario Del-Toro-Equihua; et al. (Microbiology Research)
The severity of adenovirus infection or the success of adenovirus-vectorized gene therapy largely depends on the efficiency of viral entry into cells. Various drugs can alter viral entry. This study evaluated the effects of dexamethasone, paracetamol, diclofenac, ibuprofen, and ketorolac on adenovirus entry into cells in vitro and in vivo. SiHa cell cultures pretreated with dexamethasone, paracetamol, diclofenac, ibuprofen, ketorolac, or no drug were exposed to the Ad-BGal vector. The percentage of cells showing vector entry was quantified microscopically. In vivo, BALB-C mice pretreated for 7 days with the drugs or no drug were exposed to the Ad-BGal vector intravenously (IV) or via oral (VO). Organs showing vector entry were identified by X-Gal staining and eosin counterstaining. Hepatic areas with adenovirus entry were quantified in µm2. Dexamethasone, paracetamol, and ibuprofen increased adenovirus entry both in vitro and in vivo. Diclofenac increased entry only in vitro. Ketorolac did not affect adenoviral entry. The liver exhibited the most significant changes, with dexamethasone, paracetamol, and ibuprofen increasing adenovirus entry the most. Oral administration of the vector showed that dexamethasone increased its entry into the pharynx. Some physicochemical properties of the drugs (MW (g/mol), LogP, MR [cm3/mol], tPSA, CMR, LogS, and ClogP) were analyzed, and their possible implications on cell membrane properties that could potentially influence adenovirus entry through mechanisms independent of cellular receptors were discussed. Anti-inflammatory drugs could alter adenoviral infections and adenovirus vector-based gene therapies, necessitating further research.